Społecznie odpowiedzialne działania przedsiębiorstw jako odpowiedź na współczesne problemy w organizacjach - przykłady dobrych praktyk w polityce personalnej - Klimkiewicz, Katarzyna (Corporate Social Responsibility as Key Part of an Employer's HR Strategy - Facing Contemporary Challenges in Business Environment, 2009)
Corporate Social Responsibility (CSR) is important for companies not only because of its aspects regarding communication and its positive influence on the companies' brand. Nowadays companies have to face many and constant changes: demographic changes as well as open international labour markets together with an increasing level of mobility makes it more and more difficult for employers to find and recruit the best employees. The question is: how can a company attract potential candidates and motivate current employees to stay? One possible answer could be introducing specific HR strategies based on CSR criteria. This article refers to the best practice examples from work-life balance, diversity management and employee volunteering.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 197-210